Balancing Need and Feasibility: Stakeholder Insights on Frequent Blood Glucose Monitoring in Indonesia - Rinda, Agnes Christie; Athiyah, Umi; Hermansyah, Andi (Borneo Journal of Pharmacy, 2025)
Patients with type 2 diabetes mellitus require regular evaluation of the medication's effectiveness and safety through blood glucose and HbA1c testing. This continuous monitoring is one of the primary roles of pharmacists in collaboration with physicians and supported by health insurance to examine the fluctuation patterns of blood glucose levels in response to diabetes medications. This study aimed to identify the need and feasibility of frequent blood glucose monitoring from the perspective of physicians, pharmacists, national health insurance officials, and diabetes patients. A qualitative study using semi-structured interviews was conducted in six Public Health Centers and seven pharmacies in Banjarmasin, Indonesia, from November 2022 to September 2023. A total of twenty-one respondents were included in this study. Data were tape-recorded, transcribed verbatim, and categorized using manual thematic content analysis. This study reveals that inappropriate patient conditions, irregular visits to Public Health Centers, patients' negative emotions, limitations in self-monitoring blood glucose, and lack of patients' knowledge create barriers to conducting monitoring of diabetes. On the other hand, the frequent blood glucose and HbA1c testing was supported by positive perceptions of the importance of testing, ease of access, and the active roles of physicians, pharmacists, and insurance officials. The barriers and facilitators of continuous diabetes medication monitoring are key factors that pharmacists, physicians, and insurance officials should consider to ensure that medication effectiveness and safety are monitored effectively.